Do Safety Education Show in Implementation of Health and Safety Standard? - Fadhilah, Syavirra; Rindiantika, Orin; Nugrahani, Rizqika Aprilia; Ningrum, Putri Oktaviana Wahyu; Mayningsih, Indri; Laela, Hermi Nur (Universitas Negeri Semarang, 2023)
Emergency is an unplanned event that can cause death or serious injury to people affected, shutdown/disrupt work processes, and cause physical and environmental damage. Disasters can be caused by natural disasters and human error, and are usually emergencies in nature. This study aims to obtain an objective description and evaluate the safety situation at building of research centre as an emergency response effort to minimize the risk of loss during an emergency. This research was conducted at the building of research centre building using a comparative descriptive research design and using a case study research design. Data collection process was carried out primarily by field observations and interviews with visitors and workers. Based on the observations that have been carried out in the building of research centre, the results are that the implementation of the disaster protection and prevention system consisted of 29 points, i.e., 4 active protection components and 8 components of rescue facilities. Hence, the conclusion is that the disaster management in building of research centre still needs a lot of improvements, due to some shortages in the disaster management facilities.